Prevalence of E. coli Associated Diarrhoea in Goats in Different Areas of Chhattisgarh, India - Rashmi S. Kashyap; S.L. Ali; Jasmeet Singh; Sanjay Shakya; Sushil Kumar Maiti; Hamesh Kumar Ratre; Shailendra Kumar Tiwari; Nitin E. Gade; Nidhi Rawat; Prafulla Kashyap (Archives of Current Research International, 2024)
Aims: The present study was conducted in four different districts of Chhattisgarh, viz. Durg, Raipur, Rajnandgaon and Dhamtari, to study the prevalence of E. coli associated diarrhoea in goats. Study Design: Field study. Place and Duration of Study: Faecal samples from diarrhoeic goats were collected from 04 different districts of Chhattisgarh (Durg, Raipur, Rajnandgaon and Dhamtari) during June 2023 to May 2024. Methodology: A total of 200 faecal samples were collected from diarrhoeic goats and screened for the presence of E. coli. The faecal samples were processed for microbiological isolation and identification of E. coli isolates based on the cultural, morphological and biochemical characteristics. Results: The overall prevalence of E. coli associated diarrhoea in goats was 72% (n = 144/200). The study indicated a higher prevalence in Dhamtari (32.64%), while the least prevalence was recorded in Rajnandgaon (16.67%). Younger goats (57.64%) were more frequently affected as compared to adult ones (42.36%). The study also revealed a greater prevalence in female goats (61.11%) than male goats (38.89%). E. coli was more prevalent in diarrhoeic goats, during the summer season (45.83%), followed by rainy season (32.64%) and winter season (21.53%). Based on breed, the higher prevalence was observed in the Anjori breed (35.42%). Goats reared with poor hygienic conditions (54.86%) were more commonly affected than goats reared under moderate (34.03%) and good (11.11%) hygienic conditions. Conclusion: The study concludes that E. coli associated diarrhoea is highly prevalent among goats, affecting 72% of those tested. Younger and female goats, particularly in Dhamtari and reared under poor hygiene, were most commonly affected. Seasonal variations also revealed a higher prevalence in summer season. Further studies are warranted in relation to the various serotypes and zoonotic potential of E. coli responsible for diarrhoea in goats. Possible variations in more diverse geographic zones need to be explored to propose an effective control and preventive protocol against E. coli associated diarrhoea in goats, which will eventually reduce the loss in terms of health and production in goats as well as the financial losses caused to the goat rearers.